Pengaruh Pemberian Contrast Bath dengan Elevasi Kaki 30 Derajat terhadap Penurunan Derajat Edema pada Pasien Congestive Heart Failure - Budiono Budiono; Rini Slamet Ristanti (Health Information : Jurnal Penelitian, 2019)
Congestive heart failure, which is the inability to pump blood around the body which causes the walls to be unable to pump adequately. The aim of this study was to ascertain the effect of a contrast bath with a foot elevation of 30 º on edema reduction in patients with congestive heart failure at Wafa Husada Hospital, Kepanjen. The design in this study is quasi experimental with the control group design is not equivalent. The population was patients with congestive heart failure, the sample was used consecutive sampling. 34 respondents divided into two groups, 17 respondents 'intervention groups and 17 respondents' control groups. The resulting Mann-Whitney P value = 0.027 (P <0.05) represented a significant reduction in Bath contrast edema with 300 feet elevation in the intervention group and control group patients with congestive heart failure. Based on the results of this study, it is expected to apply a bath contrast with an elevation of 30 º in nursing services to reduce the degree of edema in patients with congestive heart failure.